Sexual Dimorphism of Kisspeptin and Neurokinin B Immunoreactive Neurons in the Infundibular Nucleus of Aged Men and Women - Hrabovszky, Erik; Molnar, Csilla S.; Sipos, Mate; Vida, Barbara; Ciofi, Philippe; Borsay, Beata A.; Sarkadi, Laszlo; Herczeg, Laszlo; Bloom, Stephen R.; Ghatei, Mohammad A.; Dhillo, Waljit S.; Kallo, Imre; et al. (Frontiers in Endocrinology, 2011)
The secretory output of gonadotropin-releasing hormone (GnRH) neurons is critically influenced by peptidergic neurons synthesizing kisspeptins (KP) and neurokinin B (NKB) in the hypothalamic infundibular nucleus (Inf). These cells mediate negative feedback effects of sex steroids on the reproductive axis. While negative feedback is lost in postmenopausal women, it is partly preserved by the sustained testosterone secretion in aged men. We hypothesized that the different reproductive physiology of aged men and women is reflected in morphological differences of KP and NKB neurons. This sexual dimorphism was studied with immunohistochemistry in hypothalamic sections of aged human male (≥50 years) and female (>55 years) subjects. KP and NKB cell bodies of the Inf were larger in females. The number of KP cell bodies, the density of KP fibers and the incidence of their contacts on GnRH neurons were much higher in aged women compared with men. The number of NKB cell bodies was only slightly higher in women and there was no sexual dimorphism in the regional density of NKB fibers and the incidence of their appositions onto GnRH cells. The incidences of NKB cell bodies, fibers and appositions onto GnRH neurons exceeded several-fold those of KP-IR elements in men. More NKB than KP inputs to GnRH cells were also present in women. Immunofluorescent studies identified only partial overlap between KP and NKB axons. KP and NKB were colocalized in higher percentages of afferents to GnRH neurons in women compared with men. Most of these sex differences might be explained with the lack of estrogen negative feedback in aged women, whereas testosterone can continue to suppress KP, and to a lesser extent, NKB synthesis in men. Overall, sex differences in reproductive physiology of aged humans were reflected in the dramatic sexual dimorphism of the KP system, with significantly higher incidences of KP-IR neurons, fibers and inputs to GnRH neurons in aged females vs. males.